The Role of Imaging in the Management of Renal Masses - Sari, Jiaali Ratna (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
The widespread availability of cross-sectional imaging is responsible for the increased detection of small, usually asymptomatic renal masses. More than 50% of renal cell carcinomas (RCCs) represent incidental findings on noninvasive imaging. Multimodality imaging, including conventional US, contrast-enhanced US (CEUS), multiparametric CT and MRI (mpMRI) is essential in diagnosing and characterizing renal masses, but also provides information regarding its prognosis, therapeutic management, and follow-up. In this review, the imaging data for renal masses that urologists require for accurate treatment planning will be discussed. The roles of US, CEUS, CT and mpMRI in the detection and characterization of renal masses, RCC staging and follow-up of treated or untreated local RCCs will be presented. The role of percutaneous image-guided ablation in the management of RCC will also be reviewed.